KEANEKARAGAMAN JENIS TUMBUHAN TINGKAT POHON PADA HUTAN ADAT GUNUNG BERUGAK DESA MEKAR RAYA KECAMATAN SIMPANG DUA KABUPATEN KETAPANG - Jupendi, Ignasius Kamila; Manurung, Togar Fernando; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2017)
Gunung Berugak Customary Forest of Mekar Raya Village in Simpang Dua Sub District of Ketapang Regency became a natural forest area whose diversity of tree species is high. Around the area of Gunung Berugak Customary Forest, there is illegal logging that could threaten the diversity of plant species. So far, the data on the diversity plant species in the forest area have not been recorded properly. Therefore, this research was conducted with the aim of describing and analyzing vegetation levels of the dominant trees in the forest area of Gunung Berugak Customary forest. This study used survey method with a transects. The determination of the observation transects used purposive sampling. The results of research on transects I, II, III, IV, and V showed that the highest INP was the species of Keladan (DryobalanopsÂ  beccarii Dyer), the dominance value index (C) was in the low category, the species diversity index (H) was in the high category. The trees that serve as the structure of Gunung Berugak Customary Forest were dominated the species of keladan (DryobalanopsÂ  beccarii Dyer).Keywords : Customary Forest, Diversity, Gunung Berugak, Mekar Raya Village, Trees.